(untitled) (Colombia Medica, 2008)
Introduction: Preliminary studies have showed close relations among southwest human populations and Andean region leaving it consequences in ethnic admixe process. However, this wide process of racial admixture today it is not exist sufficient information to define structure and genetic diversity for each region and Colombian population in general. Objectives: The principal goal from this study was to determinate the genetic structure and diversity present into human populations from Andean and Southwest Colombia regions. Methods: This study was realized by characterization allelic frequencies of 12 autosomal STR’s and six RFLP’s of mtDNA presents in 472 individuals from three ethnics groups: Caucasoids, Afroamericans and Amerindians. Results: mtDNA haplotypes presents in Afrodescends sample was 15% and 43% typical Amerindian and African markers respectively; the genetics diversity analysis shows a value of 0.72 in Pijao indigenous, these values are close to diversity index of mestizos from Cali (0.75). AMOVA of allelic frequencies from 12 STR’s shows that genetic structures don’t was significatively different (FST de 0.032); in addition it’s to exhibit high endogamy in mestizos from Caldas sample (0.43) and Coyaima indigenous (0.34). Conclusions: was established genetic structure for southwest Colombian population. Additionally, the results confirm the mixing process and the genetics flow among many populations groups from Andean and southwest Colombia regions.